COMPARATIVE CHARACTERISTICS OF ACTIVITY IN PROFESSIONAL SELF-EDUCATION OF STUDENTS OF I-V COURSES PEDAGOGICAL UNIVERSITY - N.Yu. Dudnik (Academy of Cognitive and Natural Sciences, 2008)
The article describes the development of future teachers' activity in the process of selfeducation from first to last course of the university.